Microporous Layer Degradation in Polymer Electrolyte Membrane Fuel Cells. Issue 6 (12th April 2018) - Liu, Hang; George, Michael G.; Ge, Nan; Muirhead, Daniel; Shrestha, Pranay; Lee, Jongmin; Banerjee, Rupak; Zeis, Roswitha; Messerschmidt, Matthias; Scholta, Joachim; Krolla, Peter; Bazylak, Aimy
Abstract : In this work, microporous layer (MPL) degradation was investigated through the characterization of polymer electrolyte membrane (PEM) fuel cell performance and in situ liquid water visualizations. While both the MPL and carbon fiber substrate underwent ex situ carbon corrosion-based degradation, the degradation of the MPL has the most significant impact on the electrochemical performance and the liquid water distribution within the operating PEM fuel cell. Specifically, MPL degradation resulted in larger quantities of liquid water accumulation within the gas diffusion layer (GDL), and we attributed this accumulation to the loss of MPL hydrophobicity caused by the carbon corrosion-based degradation process. The increased liquid water accumulation led to increased mass transport resistances and performance losses at high operating current densities (> 1.5 A/cm 2 ). With increasing current density, the liquid water saturation profile converged to an upper threshold within GDLs with MPLs, whereas an upper liquid water saturation threshold was not observed for GDLs without MPLs. Predictions of long-term performance characteristics of PEM fuel cells should be informed by the proneness of the MPL to carbon corrosion degradation.